Keputusan Pembelian Ditinjau dari Store Atmosphere, Variasi Produk, dan Fasilitas Kedai Kopi Cold ‘N Brew Wahidin Surakarta - Arthamevia Farah Damayanti; Sudarwati Sudarwati; Istiqomah Istiqomah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the effect of store atmosphere variables, product variations, and facilities on purchasing decisions at Kedai Kopi Cold 'N Brew Wahidin Surakarta. This type of research uses a quantitative descriptive approach, data collection techniques using observation, questionnaires, and literature studies. The research sample used accidental sampling technique as many as 100 respondents with an infinite population. The research method uses multiple linear regression with data analysis techniques using validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple linear regression hypothesis testing, f test, t test and determination test. With SPSS analysis tool version 25. The results in this study indicate that the Store Atmosphere, Product Variations, and Facilities have a simultaneous effect on Purchase Decisions and the Store Atmosphere, Product Variations, and Facilities have a positive and significant effect on Purchase Decisions, respectively. Keywords: Purchase Decision, StoreOAtmosphere, ProductOVariation, and Facilities